(3OjhGf GdQGhfOis - (3GeGe GdOjf aVd Gddg Hf Ydj GdMSfj GdQGhfOj GdbGTGfj,J (B570 (3g` s
(3ChdgG (B:s
(3bGd GdQGhfOi GdbGTGfi jeOM GdUGMH GdSYjO bhGe GdOjf CHG GdbGSe GdfGUQ Hf Ydi hCfTOg EjGgG ai OGQ GdhRGQI MKhG GdeWi agPG GdUHM bO MKhG hUaa GdGab ef CfhGQg WQQkG s
(3BNQgG (B:s
(3GbHd cGdHOQ ai eOGQg bO Je OjhGf GdQGhfOi s
(3GdfSNI HgG MhGTs
(3cJHJ Chd UaMI HNW Ke cJH HGbi GdeNWhW HNW eNGdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B75s
(3eUOQ GbJfGA GdCUd (B:s
(3cJHNGfI edi edc (B(109) s
Keywords: (3GdCOHs